2010
DOI: 10.1387/ijdb.103202rk
|View full text |Cite
|
Sign up to set email alerts
|

Role of mitochondrial DNA replication during differentiation of reprogrammed stem cells

Abstract: Mitochondrial DNA (mtDNA) is a 16.6 kb genome that encodes for 13 of the 100+ subunits of the electron transfer chain (ETC), whilst the other subunits are encoded by chromosomal DNA. The ETC is responsible for the generation of the majority of cellular ATP through the process of oxidative phosphorylation (OXPHOS). mtDNA is normally inherited from the population present in the mature oocyte just prior to fertilisation. However, following somatic cell nuclear transfer (SCNT), mtDNA can be transmitted from both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 169 publications
0
8
0
Order By: Relevance
“…During neural differentiation of mouse (15) and human (63) ESCs, mtDNA copy number reduces, which allows progenitor cells to establish the ‘mtDNA set point’, from which the mitochondrial complement may be expanded in a cell specific manner (64). The ‘mtDNA set point’ was established in divergent ESCs although, during downstream differentiation, there were cell line specific differences in mtDNA copy number, PolgA expression and DNA methylation profiles for PolgA when compared with non-divergent controls.…”
Section: Discussionmentioning
confidence: 99%
“…During neural differentiation of mouse (15) and human (63) ESCs, mtDNA copy number reduces, which allows progenitor cells to establish the ‘mtDNA set point’, from which the mitochondrial complement may be expanded in a cell specific manner (64). The ‘mtDNA set point’ was established in divergent ESCs although, during downstream differentiation, there were cell line specific differences in mtDNA copy number, PolgA expression and DNA methylation profiles for PolgA when compared with non-divergent controls.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, mtDNA haplogroups appear to affect cellular function. Work on mouse ESCs has shown that in both undifferentiated and differentiating cells, the mitochondrial haplogroup has a significant impact on the expression of genes involved in pluripotency and differentiation, and does consequently influence the capacity of the cells to differentiate (Kelly and St John, 2010, Kelly et al., 2013). In the human, recent work in the context of mitochondrial replacement in oocytes indicated that some haplogroups can modify the growth dynamics of hESCs, resulting in a growth advantage that can lead to a culture takeover (Kang et al., 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…During early mammalian development, there are significant reductions in mtDNA copy number as mtDNA passes from the fertilized oocyte into the inner cell mass and into its derivatives, embryonic stem cells (ESCs) [15, 16], which establishes the mtDNA set point. The mtDNA set point ensures that undifferentiated cells have a small population of mtDNA, which is then expanded in a cell‐specific manner later during differentiation in order that specialized cells can meet their specific needs for OXPHOS‐derived ATP [15, 17, 18]. Consequently, undifferentiated ESCs rely predominantly on glycolysis to produce ATP [19, 20], although not exclusively [20, 21].…”
Section: Introductionmentioning
confidence: 99%